A Quantitative Study on The Scientific Literacy Skills of Prospective Biology Teachers - Laras Firdaus; Ibrohim Ibrohim; Sri Rahayu Lestari; Masiah Masiah; Sri Nopita Primawati; Hunaepi Hunaepi (Jurnal Penelitian Pendidikan IPA, 2023)
Scientific literacy skills are very important skills in life, not only related to academic aspects, but also in real life. Therefore, science literacy skills become a goal in 21st century education. This study aims to investigate the level of scientific literacy skills of biology prospective teacher, and to find out whether there are significant differences in scientific literacy skills of biology prospective teacher based on semester. In this study, there were 69 prospective biology teachers as voluntary respondents, consisting of 17 (2nd semester), 25 (4th semester), and 27 (6th semester). The Test of Scientific Literacy Skills (ToSLS) is an instrument used to measure scientific literacy skills. Furthermore, the data were analyzed descriptively and multivariatly using SPSS 22 at the 5% significance level. Based on the results of the analysis, it can be concluded that our participants' scientific literacy skills were not significantly different. In general, our participants' scientific literacy skills were low in the aspect understanding of element research design, creating graphs, solving problems using quantitative skills, and justify inferences, predictions, and conclusions based on quantitative data, and semesters have no significant effect on scientific literacy skills. Then, the recommendations for the results of this study are described briefly in the conclusion section